Democratization and Development in Nepal (Himalayan Journal of Sociology and Anthropology, 2017)
Democratization and development are intrinsically related to each other. There is very little literature on the relationship between democratization and development, especially after major political movements in Nepal. Therefore, this paper focuses on impacts of democratization on development activities. This is based on descriptive analysis of the Nepalese censuses after 1950s, periodical demographic surveys and a review of official documents. Democratization in Nepal has resulted in changes in Nepalese society, especially in the areas of education, health, transportation, practices in elimination of caste differentials, and migration and remittance inflow into the country. This paper is expected to have importance for policy implications from holistic perspectives.Himalayan Journal of Sociology & Anthropology - Vol. VII (2016), Page: 141-154